A Meta-Methodological Study of Dutch and Belgian PHDs in Social Security Law: Devising a Typology of Research Objectives as a Supporting Tool. Issue 3 (September 2015) - Kestemont, Lina
This article presents a typology of research objectives for legal scholarship in response to the strong call for research on legal methodology. Based on an in-depth literature study, the possible research objectives of legal scholarship are classified, labelled and discussed. In conjunction with the theoretical clarification of the typology, the article also provides concrete examples of research objectives discerned in Dutch and Belgian PhDs in social security law. The development of the typology presented in this article forms part of a broader PhD project aiming to apply a 'bottom-up' approach to research on legal methodology. In order to do this, the project identifies which research objectives and research methods have been used in a representative sample of legal research in the field of social security law. Looking into existing research on social security law makes it possible to grasp the ways in which research is being conducted in this particular branch of law. The sample analysed includes all PhDs on social security law defended at all Dutch or Belgian Law Faculties between 1945 and 2012. The typology discussed in this article then serves as a supporting tool for the analysis of the selected PhDs on social security law.